(untitled) (Czech Journal of International Relations, 2001)
The Northern Dimension: An Assessment and Future Development. International Conference Organized by the Konrad Adenauer Foundation and the Latvian Institute of International Affairs. December 6, 1999, Riga. Edited by Atis Lenjinš and Jörg-Dietrich Nackmayr . 1st ed. Riga: Konrad Adenauer Stiftung; Latvian Institute of International Affairs, 2000, 88 stran, ISBN 9984-583-26-0. Signatura knihovny ÚMV De 47 359.